Mobile Toolbox sequences task: development and validation of a remote, smartphone-based working memory test - Slotkin, Jerry; Kaat, Aaron J.; Young, Stephanie Ruth; Dworak, Elizabeth M.; Novack, Miriam A.; Shono, Yusuke; Adam, Hubert; Nowinski, Cindy J.; Pila, Sarah; Hosseinian, Zahra; Varela Diaz, Maria; Almonte-Correa, Anyelo; et al. (Frontiers in Psychology, 2025)
ObjectiveThe ability to assess cognitive skills remotely is increasing with the widespread use and availability of smartphones. The Mobile Toolbox (MTB) is a measurement system that includes Sequences, a new measure of working memory designed specifically for smartphones. This study describes the development of Sequences and presents the studies conducted to evaluate its psychometric properties.MethodsWe developed a new measure of working memory that can be self-administered remotely using an iOS or Android smartphone. In Sequences, a series of numbers and letters are shown on the screen one at a time, and the participant must first tap the letters they see in alphabetical order, followed by tapping the numbers in ascending numerical order. The Sequences measure was evaluated for usability and feasibility across two pilot studies and then assessed in this validation study (which included a total sample size of N = 1,246). Psychometric properties of the new measure were evaluated in three studies involving participants aged 18–90 years. In Study 1 (N = 92), participants completed MTB measures in a laboratory setting. They were also administered both an equivalent NIH Toolbox (NIHTB) measure along with external measures of similar constructs. In Study 2 (N = 1,007), participants were administered NIHTB measures in the laboratory and then completed MTB measures remotely on their own devices. In Study 3 (N = 147), participants completed MTB measures twice, remotely on their own devices, with a 2–week interval between sessions.ResultsSequences exhibited moderately high correlations with a comparable NIHTB test and external measures of a similar construct, while exhibiting a lower correlation with an unrelated test, as hypothesized. Internal consistency was high, but test-retest reliability was moderate. When controlling for age, phone operating system (iOS vs. Android) and sex assigned at birth did not significantly impact performance; however, there was a significant difference between individuals who completed college and those with a high school education or lower.ConclusionThe results support the validity of Sequences as a measure of working memory for remote self-administered use. The internal consistency was strong, with moderate test-retest reliability that is likely a function of the test's unproctored self-administration method. The findings suggest that Sequences is appropriate for use with adults aged 18–90 years in remote self-administered designs that focus on group results.